The tectonic significance of peri-Gondwanan Late Neoproterozoic-Early Palaeozoic felsic peraluminous magmatism - García Arias, M. (2024)
We provide a thorough review of the literature on peraluminous magmatism of Late Neoproterozoic and Early Palaeozoic (mostly Late Cambrian-Middle Ordovician) age cropping out in many places around the world (SW South Africa, NE Patagonia, NW Argentina, Colombia, SE Mexico and Guatemala, the European Variscan Massifs and from Turkey to northern Burma through Tibet). Petrographically, these volcanic and plutonic rocks contain K-feldspar phenocrysts and sometimes smaller bluish-quartz phenocrysts in a glassy/fine-grained (volcanic/subvolcanic) or medium- to coarse-grained (plutonic) matrix of quartz, plagioclase, K-feldspar and biotite, with other Al-bearing phases such as muscovite and garnet as minor phases. Notably, amphibole is conspicuously absent. Geochemically, these dacitic (tonalitic) to rhyolitic (granitic) rocks are silica-rich, peraluminous and with a strongly crustal Sr-Nd isotopic signature, pointing to S-type magmatism, but they also show characteristics of I-type subduction (a trace element signature typical of continental-arc magmatism) and A-type (enrichment in Ga) magmatism. A prominent geochemical feature is a marked depletion in Sr, resulting in low to very low Sr/Y ratios (usually <5). This, together with flat HREE slopes, suggests melting at low pressures. The arc signature is inherited from their crustal sources, which may comprise an old crustal basement and sediments derived from Pan-African and from Andean-type orogenic belts. Coeval, volumetrically minor mafic rocks are also common in many outcrops and are part of a bimodal sequence. Researchers have mostly attributed this magmatism to extensional tectonics in a back-arc setting, where the upwelling of the asthenospheric mantle triggered the high-temperature-low-pressure partial melting of a largely metasedimentary (upper continental) crust with little or no contribution from the mantle. In a reconstruction of Early Palaeozoic Gondwana, all outcrops are situated in peri-Gondwanan terranes, implying that they are related to (and the consequence of) rifting processes that led to the opening or aborted opening of several oceans (Rheic, proto-Tethys), reflecting a common evolution of the margin of Gondwana during the Cambrian and Ordovician. Given the similarities in petrography and geochemistry (major and trace elements and Sr-Nd isotopes) and the very large volume, several silicic Large Igneous Provinces have been proposed for some sectors, and the possibility that the entire magmatism comprises a single LIP is evaluated. Although correlations of this magmatism in different regions have been established previously, to our knowledge, this is the first study to integrate detailed petrographic, geochemical and geochronological data from all outcrops and to conclude that the peraluminous porphyritic magmatism reviewed here is the main magmatic expression of extension in the peri-Gondwanan area during the Early Palaeozoic.